SUNDISH flakes: An innovation in local-ingredient flakes made from breadfruit flour and pigeon pea flour as a supplementary feeding program for children - Marito Gracia Sitanggang; Ni Nyoman Laksmi Prasnayani; Gusti Ayu Kadek Diah Puspawati (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Stunting is a chronic nutritional condition that remains a significant public health concern in Indonesia, particularly among children under five years of age. Effective prevention requires appropriate nutritional interventions through supplementary feeding that is nutrient dense, higher in protein, affordable, acceptable to children, and supported by scientific evidence. Many existing supplementary feeding products are still less favored because their taste, aroma, and texture do not align with children’s preferences and their use of local food resources remains limited. Methods: This study employed a Completely Randomized Design with five formulations of pigeon pea flour and breadfruit flour in flakes production, followed by sensory evaluation, texture, and color analyses to determine the best treatment. The selected formulation was further analyzed for protein, moisture, and ash contents using Kjeldahl and gravimetric methods, while the data were statistically evaluated using ANOVA, DNMRT, and independent t-test. Findings: Products were formulated in five proportions of breadfruit flour to pigeon pea flour, namely (85%:15%, 70%:30%, 55%:45%, 40%:60%, and 25%:75%). Sensory evaluation on color, aroma, texture, taste, and overall acceptance was conducted by 25 panelists and analyzed using Analysis of Variance followed by Duncan New Multiple Range Test at a five percent significance level. The most preferred formulation was further analyzed for protein, ash, and moisture content and compared with commercial supplementary feeding flakes using Independent t-test analysis. The formulation containing 40% breadfruit flour and 60% pigeon pea flour obtained the highest scores for texture, taste, and overall acceptance and showed favorable chemical characteristics with protein 10.543%, ash 2.38%, and moisture 5.27%, with protein significantly higher than commercial products which contain 7.173%. Conclusion: These findings indicate that Sundish Flakes has promising nutritional quality and sensory acceptance, making it relevant to support efforts in stunting prevention through improved local food utilization. Novelty/Originality of this article: This study develops a high-protein supplementary cereal from locally sourced breadfruit and pigeon pea flours to improve sensory acceptance and nutritional quality for stunting prevention among Indonesian children.